PENGARUH DIGITAL PAYMENT DAN FINANCIAL LITERACY TERHADAP FINANCIAL MANAGEMENT - Muhammad Khanif Mustafid; Maretha Ika Prajawati (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2026)
The development of digital payment technology encourages students to make transactions more practically, but this convenience is not always accompanied by adequate financial management skills. This study aims to analyze the influence of digital payment and financial literacy on the financial management behavior of students in the Management Study Program at UIN Maulana Malik Ibrahim Malang class of 2022.The study employs a descriptive quantitative approach using purposive sampling, involving 72 respondents who actively use digital payments. Data analysis includes validity and reliability tests, classical assumption tests, and multiple linear regression. The results show that digital payments do not have a significant effect on financial management behavior (sig. 0.381 > 0.05), while financial literacy has a positive and significant effect (sig. < 0.001). The coefficient of determination (R²) value of 0.554 indicates that the two independent variables are able to explain 55.4% of the variation in students' financial management behavior. These findings confirm that even though the use of digital payment services is quite widespread, healthy financial behavior is more influenced by an individual's level of financial understanding. Therefore, improving financial literacy is a crucial aspect in encouraging wiser financial management behavior amid the increasing ease of access to digital payment services.